PENGGUNAAN MEDIA QUIZIZZ DALAM PENERAPAN KOSAKATA BAHASA ARAB - Hilmy, Baso (Transformasi : Jurnal Kepemimpinan & Pendidikan Islam, 2024)
Technological advances currently in the industry 4.0 era require educators to be more active and creative in choosing learning media. This research aims to describe the use of quizizz as an alternative media in applying Arabic vocabulary. This research was carried out using a qualitative descriptive approach through the literature study method.  The research results show that quizizz is a very easy, effective and interesting medium to use in online-based Arabic language evaluation and learning activities. This application can be implemented directly or as an assignment. The features available in this application can be used for Arabic language evaluation and learning activities, such as applying Arabic vocabulary. This research contributes to the development of Arabic language learning media, especially in Madrasas and religious universities.